Towards Computational Synergy: Present State-of-the-art of Mobile Cloud Computing - , Dr. Maligela Ussenaiah, Kolluru Venkata Nagendra, (International Journal of Scientific Research and Management (IJSRM), 2015)
Cloud computing has emerged as a new computing paradigm that has potential to commoditize computing resources in pay per use model. It is the technology that is on top of virtualization for affordable service models. With ever growing mobile technologies cloud computing is expanded to mobile devices as well. This has led to the concept of mobile cloud computing which makes the resource constrained mobile devices more powerful as they can connect to cloud resources and outsource the storage and computing to cloud. Thus mobile devices became ubiquitous and used by people of all walks of life, mobile cloud computing is growing in rapid pace. Since mobile devices are inherently vulnerable to various kinds of attacks, there are security and privacy issues in mobile cloud computing. The knowledge of ins and outs of mobile cloud computing, or in other words, the present state-of-the-art of mobile cloud computing in terms of architectures, application models, security and other challenges can help individuals and organization to have expert decisions. Towards this end, this paper throws light into the same to bring about useful insights pertaining to mobile cloud computing as the future generation computing model.